Yazi, yafrikiin ornuudyn yard tvmnii ev syanyayany negdel bekhjtvgei!
Two holding hands, surrounded by flags of African and Asian countries. Rising sun in background Original title: Язи, яфрикийн орнуудын ярд тvмний эв сяняяны нэгдэл бэхжтvгэй! Suggested translation: Strengthen the unity of the Yiyi and the Asian countries! PO-2156